Public debt and generational balance in Austria - Christian Keuschnigg; Mirela Keuschnigg; Reinhard Koman; Erik Lüth; Bernhard Raffelhüschen (Institute for Advanced Studies (IHS), 2000)
Based on Austria's fiscal stance in 1995, we compute the generational accounts for currently living as well as future generations. The results reveal the existence of an enormous intergenerational imbalance in favor of currently living generations. Total public sector liabilities may be more than five times as high as the officially recorded level of public debt. Without any action, future generations would face life-time net taxes that are about 65 percent higher than the tax burden of a current newborn. If the government could fully and permanently retain the expenditure cutting and revenue raising effects of the 1996 fiscal consolidation package and the 1997 pension reform, then it might be able to significantly reduce the intergenerational liabilities. However, enacting both the recent tax reform 2000 and the reform of the family support scheme would increase again the fiscal imbalance and intergenerational inequity of fiscal policy in Austria.
Keywords: E6; H5; H6; 330; fiscal policy; social security; public debt; enerational accounting; Öffentliche Schulden; Intergenerative Belastungsrechnung; Haushaltskonsolidierung; Rentenreform; Steuerreform; Österreich